Communicating to lead and motivate - Sharbrough William C. (Corporate governance collection., 2017)
Effective leaders lead by communicating. It is through communication that leadership is enacted as leaders influence followers to behave in ways that achieve the leader's and the organization's goals. This book applies leadership theory and research to communication in ways that are easily understood and can be applied to any situation where individuals find themselves in a leadership position in an organization whether as a frontline or top-level leader. The book begins with a basic explanation of the leadership process and how leaders express their vision. It then looks at how leaders can create positive relationships with followers that pay off in effective performance. Next, the book investigates how leaders motivate their followers by creating follower self-efficacy, trust, and valued rewards. Then, the focus changes to the specific types of messages a leader can use to motivate followers. Leading is about change, so the book next looks at ways effective leaders communicate in leading change in organizations and at how the changing workforce is effecting how effective leaders communicate with the new workforce.